Desain Struktur Utama Suspension Building Menggunakan Balok Pelat Berdinding Penuh (Pelat Girder) - Nopendrianto, Antok; Bayzoni, Bayzoni; Husni, Hasti Riakara (Universitas Lampung, 2020)
AbstractPlate girder is a flexible structural component that composed from several plate elements. Basically, plate girder is a beam with a large cross-sectional size and a long span. Plate girder is an alternative if the largest hot rolled steel profile is insufficient to carry the working load due to its long span.This research will plan the main structure, that is girder plate for a multi-storey building with a hanging system (suspension building), and also plan the complementary components. Generally, the implementation steps of the process are collecting planning data, calculating loading, calculating the forces those worked on the structure using SAP2000, after that, designing the girder plate profile, and other components such as joint design and stiffener design, so that safe structural details are obtained.In the design that has been done, the column dimensions are obtained (h = 1500, bf = 500, tw = 8, tf = 30) mm, beam (h = 1500, bf = 450, tw = 8, tf = 30) mm, transverse stiffener ( bp = 120, tp = 8, h = 1440) mm, column-beam joints (Db = 24mm, n1 = 36 bh, n2 = 78 bh), beam-beam joints (Db = 24mm, n1 = 32 bh, n2 = 70 bh), splice joints (Db = 24mm, n1 = 26 bh, n2 = 16 bh), and base plate connections (Db = 24mm, n1 = 10 bh). Based on the design, the profile and components are quite safe to use.Keywords : Girder Plate Beam, Steel Structure, Building Structure Design, Suspension Building.